2012
DOI: 10.1016/j.vetpar.2011.08.026
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative and quantitative polymerase chain reaction (PCR) for detection of Leishmania in spleen samples from naturally infected dogs

Abstract: Because infected dogs are widely considered to be the main domestic reservoir for Leishmania infantum (syn Leishmania chagasi) parasites in Brazil, the diagnosis of canine visceral leishmaniasis (CVL) must be made both accurately and promptly. The present study attempted to standardize a conventional polymerase chain reaction (cPCR) protocol for the detection of L. infantum DNA in canine spleen samples. Quantitative PCR (qPCR) technique was used to confirm the presence of Leishmania DNA in the canine spleen fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 51 publications
0
23
0
2
Order By: Relevance
“…bone marrow, lymph nodes and spleen) makes them important for detecting this protozoon. Different studies have demonstrated high positive rates of L. infantum detection in lymph nodes (IKONOMOPOULOS et al, 2003), spleen (SOLCÀ et al, 2012) and bone marrow (FERREIRA et al, 2012) using molecular biology tests. Some of them have suggested that lymph nodes are the best biological samples for molecular diagnosis of L. infantum (IKONOMOPOULOS et al, 2003;RAMOS et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…bone marrow, lymph nodes and spleen) makes them important for detecting this protozoon. Different studies have demonstrated high positive rates of L. infantum detection in lymph nodes (IKONOMOPOULOS et al, 2003), spleen (SOLCÀ et al, 2012) and bone marrow (FERREIRA et al, 2012) using molecular biology tests. Some of them have suggested that lymph nodes are the best biological samples for molecular diagnosis of L. infantum (IKONOMOPOULOS et al, 2003;RAMOS et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Real-time PCR (qPCR) has presented high sensitivity and specificity for diagnosing and monitoring parasite loads in different biological samples (MARY et al, 2004;TUPPERWAR et al, 2008;RAMOS et al, 2012). However, based on the parasite load, it is still unclear which biological sample should be preferred in order to make a correct diagnosis (IKONOMOPOULOS et al, 2003;BARROUIN-MELO et al, 2006;SOLCÀ et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Bigeli et al (2012) blood. Leishmania parasites have a high number of kDNA minicircles copies (10,000 copies) per parasite, which increases the sensitivity of the assay (Quaresma et al 2009;Solc a et al 2012), as observed in this study with »10 0 parasite mL ¡1 .…”
Section: Discussionmentioning
confidence: 50%
“…Recently, PCR has significantly advanced with the use of quantitative real-time PCR (qPCR) that promotes a real-time and accurate quantification (Ramos et al 2012;Solc a et al 2012), and helps in confirmation of inconclusive cases of CVL, i.e. dogs not yet seroconverted, accurate detection of potential reservoirs, and determination of a decrease of the parasite load in these animals as a result of successful therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Sendo assim, o diagnóstico laboratorial pode ser realizado através do exame parasitológico direto, testes imunológicos, como imunofluorescência indireta (RIFI) ou ensaio de imunoadsorção enzimático (ELISA), métodos imunohistoquímicos e, mais recentemente, através de métodos moleculares de amplificação do ácido nucleico, como a Reação da Cadeia em Polimerase (PCR) e PCR quantitativo (Real Time PCR) (MOREIRA et al, 2007;QUEIROZ et al, 2010;SOLCÁ et al, 2012).…”
Section: Introductionunclassified